Physiotherapy Management of Post Op Recontruction Anterior Cruciate Ligament (ACL) Knee Sinistra Phase I Case Study of Silat Athletes in Boeana Physiotherapy Solo - Dewangga, Mahendra Wahyu; Saputro, Sigit; Fitriani, Dessy; Maisaroh, M (Academic Physiotherapy Conference Proceeding, 2023)
Introduction: Sports injuries refer to injuries that occur as a result of sporting activities, either directly or indirectly. Sports injuries that occur to a person will cause a sensation of pain caused by damage to the structure or function of the body, such as bones, joints, ligaments and muscles. One type of sports injury that often occurs is rupture of the anterior cruciate ligament (ACL). The ACL ligament is an important component in the knee. The main function of the ACL is to maintain stability when anterior tibial movement and internal rotation occur. Rupture is a condition when tissue is damaged or torn due to trauma. Case Presentation: The patient experienced limited movement and pain when flexing and extending the left knee accompanied by pain which made it difficult for the patient to carry out daily activities. The patient suffered an injury caused by an opponent's attack during a silat competition which resulted in a “pop” sound which made his knee ache and made it difficult to bend his knee. The patient was medically diagnosed with left knee ACL rupture. The patient complained of motion pain and tenderness in the left knee area, flexor and extensor muscle weakness, hamstring muscle spasm, decreased joint range of motion, and muscle atrophy. Management and Outcomes: Patients are given intervention in the form of phase I exercise including: quadriceps set, hamstring sets, clump sell, SLR, ankle theraband, slide heels, weight training. Before the exercise, the patient is given tens and given an ice pack after the therapy.After being given the intervention once, the results showed that there was no significant decrease in motion pain, there was no significant increase in muscle strength, there was an increase in the range of motion of the joints, there was no increase in muscle mass. Discussion: Tens aims to help reduce pain, stimulate muscle activity, and reduce swelling, phase 1 exercise therapy, namely strengthening exercises quadriceps set performed to increase strength in the quadriceps muscles, hamstring sets done to increase strength in the hamstring muscles, clump sell performed to increase strength in the gluteus muscles and stabilization of the hips, SLR to strengthen the abductor, adductor, gluteus, and hamstring muscles, ankle theraband to increase the strength of the ankle muscles (m. tibialis anterior, m. gastrocnemius, m. peroneus), slide heels performed to increase knee joint ROM and stretch leg muscles, weight training to add LGS to the knee extension movement and to reduce pain, and ice packs to reduce pain and swelling, so that it can help increase range of motion (ROM).